Preservation of Sarawak Manuscript / Amy Ngau Ing, Imilia Ibrahim, Sabariah Abd Samad... [ et.al]. - Ngau Ing, Amy; Ibrahim, Imilia; Abd Samad, Sabariah; Ismailly, ,, Norlida; Sulaiman, Sharin (2011)
The aim of this paper is to give insights on the current practices of manuscripts preservation in Sarawak. Most historical and valuable resources and manuscripts are stored and kept within the state as they are given a special right to maintain their historical resources. As there are different authorities in charge of manuscript preservation in Sarawak, the issue of effectiveness of storage and retrieval is highlighted. In understanding the situation of preservation of manuscript in Sarawak, this research is done with three research objectives. The first objective is to identify if there is any agency responsible in collecting, managing, preserving and storing manuscripts. The next objective is to know what are the methods used to ensure the safety and maintain the historical value of the manuscripts and the third objective is to distinguish the strengths and challenges of the organizations involved in preserving manuscripts in Sarawak. The strategies used in doing this research are observation and interview. Three major institutions involved in preservation of manuscripts in Sarawak were chosen to be observed. Observation was done in the premise of the organization to identify the process of preservation and storage of manuscript in the selected agencies. Besides that the websites of the organizations have also been visited to find out whether there is any exposure or promotion done for public awareness about manuscript. Interviews were also done with personnel in charge to discover the strength and challenges faced by the organizations in preserving manuscript. The finding shows that Sarawak has quite a number of manuscripts under the custody of different state authorities. Although there is a branch of a national archive in Sarawak, this branch does not have the right to keep local manuscripts. Most of the manuscripts have been preserved properly but the safekeeping of the manuscripts could be questionable.